THE FACTORS INFLUENCING GRADE-9 STUDENTS’ INTENTION TO CHOOSE CHEMISTRY BASED ON THE THEORY OF PLANNED BEHAVIOR - Hoai Minh, Thai; Hien Nhu, Do (HNUE Journal of Science: Journal of Educational Science, 2026)
This study investigates the factors influencing grade-9 students’ intention to choose Chemistry based on the Theory of Planned Behavior. Three factors were examined: attitude, subjective norms, and perceived behavioral control. The survey was conducted with 283 grade-9 students in District 1 of Ho Chi Minh City in 2024. At the time of data collection, these students were studying under the 2006 General Education Curriculum and were preparing to select elective subjects at the upper secondary level. The measurement instrument was developed from Ajzen’s framework and refined through pilot interviews. Data were analyzed with SmartPLS 4. The findings reveal that all three factors positively influence students’ intention to choose Chemistry, with attitude being the strongest predictor (β = 0.547). The study provides empirical evidence to support career guidance and subject orientation under the 2018 General Education Curriculum, while offering strategic recommendations for school leaders and teachers to enhance students’ interest and guide their subject choices in Chemistry.